The Impact of E-Procurement Implementation on Public Procurement’s Corruption Cases; Evidence from Indonesia and India - Desi Kartika (Jurnal Kajian Wilayah, 2020)
The huge spending on public procurement makes public procurement is very vulnerable to corruption. Many governments around the world have adopted Electronic Procurement (E-Procurement) to increase transparency, improve accountability, and reduce corruption with variable success. Government of Indonesia adopted E-Procurement in 2008, while Government of India introduced E-Procurement in 2012. Even though E-Procurement has been implemented for quite a long time in those two emerging countries, only limited research exist on the impact of E-Procurement in reducing procurement corruption. By using the combination between quantitative and qualitative methods, this study attempts to assess the extent to which the impact of E-Procurement implementation on procurement corruption cases in Indonesia and India. The findings suggest that Indonesian provinces with high capital expenditure ratio, are more vulnerable to corruption and implementation of E-Procurement was impactful on reducing the number of procurement corruption cases in such provinces. Meanwhile in India, the effect of E-Procurement was not impactful enough to reduce a notably large number of procurement corruption at the state governments because E-Procurement implementation at the state level in some degree was bothered by low competency and professionalization staff and also high political interference in state administrations. The study contributes to limited empirical research on the effect of E-Procurement on corruption.